DECIDE: a cluster randomized controlled trial to reduce non-medically indicated caesareans in Burkina Faso. Issue 1 (December 2016) - Kaboré, Charles; Ridde, Valéry; Kouanda, Séni; Queuille, Ludovic; Somé, Paul-André; Agier, Isabelle; Dumont, Alexandre
Abstract Background Since 2006, Burkina Faso has subsidized the cost of caesarean sections to increase their accessibility. Caesareans are performed by obstetricians, general practitioners, and nurses trained in emergency surgery. While the national caesarean rate is still too low (only 2 % in 2010), 12 to 24 % of caesareans performed in hospital are, in fact, not medically indicated. The objective of this study is to evaluate the effectiveness and analyze the implementation of a multi-faceted intervention to lower the rate of non-medically indicated caesareans in Burkina Faso. Methods This study combines a multicentre cluster randomized controlled trial with an implementation analysis in a mixed-methods approach. The evidence-based intervention will consist of three strategies to improve the competencies of maternity teams: 1) clinical audits based on objective criteria; 2) training of personnel; and 3) decision-support reminders of indications for caesareans via text messages. The unit of randomization and of intervention is the public hospital equipped with a functional operating room. Using stratified randomization on hospital type and staff qualifications, 11 hospitals have been assigned to the intervention group and 11 to the control group. The intervention will cover 1 year. Every patient who delivered by caesarean during a 6-month period in the year preceding the intervention and the 6 months following its end will be included in the trial. The change in the rate of non-medically indicated caesareans is the main criterion by which the intervention's impact will be assessed. To analyze the intervention process, a longitudinal qualitative study consisting of deliberative workshops and individual in-depth interviews will be conducted. The target outcome is a 50 % reduction in the rate of non-medically indicated caesareans. Discussion This study will provide evidence regarding the effectiveness of a multi-faceted intervention for reducing non-medically indicated caesareans in a low-income country. By combining qualitative and quantitative methods, the study's findings will allow understanding the factors that could influence the intervention process and ultimately the intended outcomes. Trial registration The DECIDE trial is registered on the Current Controlled Trials website under the numberISRCTN48510263 on January 28, 2014.